Recruitment evaluation of a gerotherapeutic randomized controlled trial testing alpha-ketoglutarate in biologically older, middle-aged adults (ABLE) - Zhi Meng Lim; Yi Ern Chew; Lihuan Guan; Weilan Wang; Muhammad Daniel A. Mahadzir; Rajkumar Dorajoo; Brian Kennedy; Elena Sandalova; Andrea B. Maier (Experimental Gerontology)
Background: Gerotherapeutic interventions that optimize the health and healthspan of biologically older, yet generally healthy adults are importance for reducing healthcare costs associated with ageing populations. It remains unclear whether recruiting middle-aged individuals with an older biological age is feasible in gerotherapeutic trials. The aim is to evaluate feasibility of recruiting biologically older yet generally healthy middle-aged adults for Alpha-ketoglutarate Supplementation and BiologicaL agE in middle-aged adults (ABLE) trial. Methods: ABLE is a double-blind, placebo-controlled randomized trial assessing the effects of 1 g sustained-release calcium alpha-ketoglutarate versus placebo over 6 months, followed by 3 months of follow up visit, in 120 generally healthy adults (with at most one chronic condition) aged 40–60 years with a higher biological age (assessed by DNA methylation clocks) than chronological age living in Singapore. Feasibility analyses were done using the recruitment metrics; recruitment rate, consent rate, eligibility rate, recruitment conversion rate, and the effectiveness of recruitment strategies. Results: Among 467 individuals who expressed interest in participation, 120 participants were enrolled in the study. The recruitment period was 223 working days. Eligibility rates were 80.3 % at pre-screening and 67.3 % at screening, with a consent rate of 66.1 %. Conversion rates were 25.7 % and 48.4 % from pre-screening and screening to enrolment, respectively. The biological age was exceeding the chronological age in 80.2 % of participants and 54.3 % reported no pre-existing health conditions. Word-of-mouth was the most effective recruitment method (36.2 %). Conclusion: ABLE demonstrated the feasibility of recruiting biologically older yet generally healthy middle-aged adults for gerotherapeutic interventions.